Fusarium oxysporum Race 1 resistance and quality traits variations in apple banana germplasm - Buregyeya, Henry; Tumuhimbise, Robooni; Matovu, Moses; Tumwesigye, Kashub S.; Kubiriba, Jerome; Nowankunda, Kephas; Tushemereirwe, Wilberforce K.; Karamura, Deborah; Karamura, Eldad; Kityo, Robert M.; Rubaihayo, Patrick (Journal of Plant Breeding and Crop Science, 2020)
Musa species, AAB genome group, commonly known as Sukali Ndizi (SND) in Uganda, has attained a substantial commercial value in the recent past owing to its superior fruit quality attributes and better prices. However, its sustainable production and productivity are highly threatened by Fusarium wilt. To facilitate large scale area expansion of this important dessert banana, the present study was carried out to identify the near-ideotypic lines of best quality fruit traits that are also resistant to Fusarium wilt. Nineteen SND ecotypes were subsequently collected from nine key SND growing districts of Uganda and evaluated in the field and laboratory for different fruit quality attributes and response to Fusarium wilt. Results showed a wide diversity among SND ecotypes for fruit-quality traits (fruit pulp texture, flavor and taste). The ecotypes were, however, not significantly different (p > 0.05) for susceptibility to FOC race 1. Cluster analysis based on organoleptic and physio-chemical properties grouped the 19 ecotypes into two major-clusters, each of which was also split into two sub-clusters. Individual subclusters summarize levels of similarity amongst the different ecotypes. The study confirmed the presence of diversity in SND germplasm that could be exploited for SND genetic improvement of the crop through hybridization and selection.
Keywords: Sukali Ndizi; Fruit-quality traits; Fusarium wilt; Ecotypes; Desert banana; Diversity